2020
DOI: 10.1016/j.lfs.2020.118513
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/AKT/mTOR signaling in gastric cancer: Epigenetics and beyond

Abstract: PI3K/AKT/mTOR pathway is one of the most important signaling pathways involved in normal cellular processes. Its aberrant activation modulates autophagy, epithelialmesenchymal transition, apoptosis, chemoresistance, and metastasis in many human cancers.Emerging evidence demonstrates that some infections as well as epigenetic regulatory mechanisms can control PI3K/AKT/mTOR signaling pathway. In this review, we focused on the role of this pathway in gastric cancer development, prognosis, and metastasis, with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
135
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(164 citation statements)
references
References 215 publications
1
135
0
1
Order By: Relevance
“…ROS inhibition can activate molecular pathways involved in cancer progression and phosphoinositide 3-kinase (PI3K)/protein kinase-B (Akt) is one of them. It has been reported that activation of PI3K/Akt axis not only promotes proliferation and metastasis of cancer cells [122][123][124][125], but also triggers chemoresistance [126][127][128][129]. Therefore, it is important to reveal the role of this molecular pathway in CP resistance of cancer cells and providing prospects for its targeting.…”
Section: Cisplatin Resistancementioning
confidence: 99%
“…ROS inhibition can activate molecular pathways involved in cancer progression and phosphoinositide 3-kinase (PI3K)/protein kinase-B (Akt) is one of them. It has been reported that activation of PI3K/Akt axis not only promotes proliferation and metastasis of cancer cells [122][123][124][125], but also triggers chemoresistance [126][127][128][129]. Therefore, it is important to reveal the role of this molecular pathway in CP resistance of cancer cells and providing prospects for its targeting.…”
Section: Cisplatin Resistancementioning
confidence: 99%
“…The PI3K/AKT/mTOR signalling pathway plays an important role in numerous diseases, including cancer. This pathway controls several key cellular processes responsible for cellular homeostasis, while aberrant activation of the pathway has been observed in human cancers 51,52 . In the skin, this pathway is crucial for skin development and homeostasis 53 .…”
Section: Discussionmentioning
confidence: 99%
“…CTAB can increase the expression of proapoptotic Bax and downregulate the expression of antiapoptotic Bcl-2, thereby increasing mitochondrial permeability. The PI3K/AKT pathway is a widely studied intracellular signaling pathway that plays an indispensable role in all malignant phenotypes (such as tumorigenesis, cancer cell proliferation, survival, migration, and chemoresistance) (33,34). According to reports, dysregulation of the PI3K/AKT pathway also plays a vital role in the occurrence and development of OS (35).…”
Section: Discussionmentioning
confidence: 99%